Evaluation of durum wheat genotypes based on drought tolerance indices under different levels of drought stress conditions - Abdulahi, Abdolvahab (Journal of Agricultural Sciences (Belgrade), 2017)
The main objectives of this study were to evaluate durum wheat genotypes for improving drought tolerance and to study relationships among different drought tolerance indices under different levels of drought stress. 22 durum wheat genotypes were evaluated in a randomized complete block design with three replications for three cropping seasons (2008-11). Different drought indices such as tolerance (TOL), mean productivity (MP), mean relative performance (MRP), stress susceptibility index (SSI), modified severity stress  index (SSSI), geometric mean productivity (GMP), stress tolerance index (STI), yield stability index (YSI), relative efficiency index (REI) and drought response index (DRI) were calculated based on yields under stress and non-stress conditions. The studied genotypes showed considerable variability in yield and tolerance to different levels of drought stress that could be exploited in durum breeding program. The results showed screening of genotypes for drought tolerance in environments with greater value of stress intensity (SI) will be more efficient in grouping of indices and genotype selection. The indices were classified into groups (G1 and G2). The Group-G1 which consisted of the indices REI, STI, MRP, GMP, DRI and YSI distinguished genotypes with higher yield in different levels of drought stress.  The durum breeding lines No. 1, 11, 10, 13, 8, 9, and 12 were superior based on Group-G1 with higher yield productivity under different level of drought stress that could be regarded for further evaluation under drought-prone environments.